2011
DOI: 10.1021/bm201554x
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymers from Vegetable Oils via Catalyst- and Solvent-Free “Click” Chemistry: Effects of Cross-Linking Density

Abstract: New monomers were prepared by introducing the azide groups in castor, canola, corn, soybean, and linseed oils. Polymerization of the azidated oils with alkynated soybean oil under thermal "click" chemistry conditions (without using a solvent or a catalyst) yielded fully cross-linked elastomers (1-5) of almost the same density (1.05 × 10(-3) kg/m(3)). The degree of cross-linking gradually increased from the castor-derived polymer (220 mol/m(3)) to the linseed-derived polymer (683 mol/m(3)). A systematic correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 35 publications
(47 reference statements)
3
63
1
Order By: Relevance
“…According to Hazer and coworkers [26][27][28][29][30][31][32][33], vegetable oils were autooxidized by exposure to sunlight or daylight in air for a given time to produce epoxides, peroxides, peroxides, and hydroperoxides in the molecular chains and were also graft copolymerized by free radical polymerization with other materials such as methyl methacrylate and styrene. Recently, the vegetable oil-based polymers have been prepared by cationic, olefin metathesis and condensation polymerization reactions, including the use of 'click' chemistry and carbon dioxide [5,[34][35][36][37]. Acrylation of epoxidized vegetable oils is one of the interesting techniques for preparing the vegetable oil-based polymers.…”
mentioning
confidence: 99%
“…According to Hazer and coworkers [26][27][28][29][30][31][32][33], vegetable oils were autooxidized by exposure to sunlight or daylight in air for a given time to produce epoxides, peroxides, peroxides, and hydroperoxides in the molecular chains and were also graft copolymerized by free radical polymerization with other materials such as methyl methacrylate and styrene. Recently, the vegetable oil-based polymers have been prepared by cationic, olefin metathesis and condensation polymerization reactions, including the use of 'click' chemistry and carbon dioxide [5,[34][35][36][37]. Acrylation of epoxidized vegetable oils is one of the interesting techniques for preparing the vegetable oil-based polymers.…”
mentioning
confidence: 99%
“…Due to economic reasons in 2004 Metabolix began to produce PHB also from plants (Jacquel et al, 2008). Soybean and linseed oils were used as substrates for monomers to produce elastomers (Hong et al, 2012) and ethylene from bioethanol (KBBE Report, 2010). In the United States, $ 310 billion was spend on bioplastics in 2002.…”
Section: Materials and Biopolymersmentioning
confidence: 99%
“…Alternatively, Shah and coworkers reported that alkynated plant oils are also accessible from the corresponding epoxidized derivatives taking advantage of the HIGHLIGHT propensity of the epoxy rings to undergo ring-opening nucleophilic addition. 81,82 A real challenge for the near future is definitively to develop new methods (e.g., catalytic dehydrogenation of alkenes) to directly transform fatty acids into alkyne derivatives under sustainability criteria.…”
Section: Thiol-yne Addition and Azide-alkyne Cycloaddition In Oleochementioning
confidence: 99%